Penerapan End-User Computing Satisfaction (EUCS) dalam Evaluasi Halodoc (Studi Kasus: Masyarakat Jalan Dipatiukur) - Andri Sahata Sitanggang; Zelgi Raidansyah; Rangga Maulana Putra; Raka Bintang Syahputra; Muhammad Farhan Rasyad (PT. Hasba Edukasi Mandiri, 2026)
This study aims to evaluate the implementation of the information system within the Halodoc application concerning the improvement of public healthcare quality and access in the Dipatiukur area, Bandung. Utilizing a descriptive quantitative approach, the research employed a survey method by distributing questionnaires to 376 Halodoc users selected through a purposive sampling technique. This was further strengthened by semi-structured interviews with 11 respondents for data triangulation. Data were analyzed descriptively based on four indicators adapted from the End-User Computing Satisfaction (EUCS) framework: ease of use, system reliability, completeness of features, and security and privacy. The results indicate a high level of user satisfaction across all indicators, with indices ranging from 84% to over 96%. These findings suggest that the implementation of the Halodoc Information System has contributed positively to enhancing public healthcare quality and access in the Dipatiukur area, although room for improvement remains in terms of technical reliability and data security enhancement.